The power of mobile banking : how to profit from the revolution in retail financial services - Krishnan, Sankar, 1967- (Hoboken, NJ. : Wiley, 2014)
This book gives banking and financial professionals a well-researched guide for becoming transformational leaders. These leaders can convert their traditional retail "branch" banks into streamlined systems that deliver personalized services to their customers' laptops, tablets, and smartphones.
Includes bibliographical references and index.
oif 16/06/15
Loan
Keywords: Internet banking; Banks and banking, Mobile